Outcomes of High-Flow Nasal Cannula Vs. Nasal Continuous Positive Airway Pressure in Young Children With Respiratory Distress: A Systematic Review and Meta-Analysis - Zhao, Xueqin; Qin, Qiaozhi; Zhang, Xian (Frontiers in Pediatrics, 2021)
Background: Continuous positive airway pressure (CPAP) has been associated with a lower risk of treatment failure than high-flow nasal cannula (HFNC) in paediatric patients with respiratory distress and severe hypoxemia. However, the publication of new trials on children younger than 2 years warrants a review and updated meta-analysis of the evidence. Methods: We conducted a systematic search in the PubMed, Scopus, and Google scholar databases for randomized controlled trials in paediatric patients with acute respiratory distress that examined outcomes of interest by the two usual management modalities (CPAP and HFNC). We used pooled adjusted relative risks (RRs) to present the strength of association for categorical outcomes and weighted mean differences (WMDs) for continuous outcomes. Results: We included data from 6 articles in the meta-analysis. The quality of the studies was deemed good. Included studies had infants with either acute viral bronchiolitis or pneumonia. Compared to CPAP, HFNC treatment carried a significantly higher risk of treatment failure [RR, 1.45; 95% CI, 1.06 to 1.99; I2=0.0%, n=6]. Patients receiving HFNC had a lower risk of adverse events, mainly nasal trauma [RR, 0.30; 95% CI, 0.14 to 0.62; I2=0.0%, n=2] than the others. The risk of mortality [RR, 3.33; 95% CI, 0.95, 11.67; n=1] and need for intubation [RR, 1.69; 95% CI, 0.97, 2.94; I2=0.0%, n=5] were statistically similar between the two management strategies; however, the direction of the pooled effect sizes is indicative of a nearly 3 times higher mortality and 2 times higher risk of intubation in those receiving HFNC. We found no statistically significant differences between the two management modalities in terms of modified Woods clinical asthma score (M-WCAS; denoting severity of respiratory distress) and hospitalization length(days). Patients receiving HFNC had the time to treatment failure reduced by approximately 3 hours [WMD, -3.35; 95% CI, -4.93 to -1.76; I2=0.0%, n=2] compared to those on CPAP. Conclusions: Among children with respiratory distress younger than 2 years, HFNC appears to be associated with higher risk of treatment failure and possibly, an increased risk of need for intubation and mortality. Adequately powered trials are needed to confirm which management strategy is better.